Utilization of Digital Marketing to Increase the Income of Micro, Small and Medium Enterprises (MSME) in Madaprama Village, Woja District, Dompu Regency - Junaidin, Junaidin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is motivated by the rapid flow of globalization which makes the development of technology towards digital technology increasingly rapid. This is an opportunity that business actors can take advantage of to penetrate the digital marketing market. This research aims to determine the role of digital marketing in increasing the income of Micro, Small and Medium Enterprises (MSMEs) in Madaprama Village, Gerung District, West Lombok Regency and to understand the obstacles and benefits of implementing digital marketing for Micro, Small and Medium Enterprises (MSMEs) actors. in Dasan Tapen Village, Gerung District, West Lombok Regency. To reveal this problem, this research uses a type of qualitative research which is useful for providing facts and data regarding the use of digital marketing to increase MSME income. From the research results, it was found that digital marketing played a role in increasing the income of MSMEs in Madaprama Village, Woja District, West Dompu Regency, this was proven by an increase in income of 33% to 59%.